When mirroring is both simple and “smart”: how mimicry can be embodied, adaptive, and non-representational - Carr, Evan W.; Winkielman, Piotr (Frontiers in Human Neuroscience, 2014)
The concept of mirroring has become rather ubiquitous. One of the most fundamental empirical and theoretical debates within research on mirroring concerns the role of mental representations: While some models argue that higher-order representational mechanisms underpin most cases of mirroring, other models argue that they only moderate a primarily non-representational process. As such, even though research on mirroring—along with its neural substrates, including the putative mirror neuron system—has grown tremendously, so too has confusion about what it actually means to “mirror.” Using recent research on spontaneous imitation, we argue that flexible mirroring effects can be fully embodied and dynamic—even in the absence of higher-order mental representations. We propose that mirroring can simply reflect an adaptive integration and utilization of cues obtained from the brain, body, and environment, which is especially evident within the social context. Such a view offers reconciliation among both representational and non-representational frameworks in cognitive neuroscience, which will facilitate revised interpretations of modern (and seemingly divergent) findings on when and how these embodied mirroring responses are employed.